Influences and mechanisms of graphene-doping on dehydrogenation properties of MgH2: Experimental and first-principles studies. (September 2015) - Zhang, J.; Yu, X.F.; Mao, C.; Long, C.G.; Chen, J.; Zhou, D.W.
Abstract: Using experimental and first-principles calculations methods, a systematic investigation was performed on the dehydrogenation properties and mechanisms of MgH2 -10 wt%G (graphene) composites acquired by ball milling. It was found that the doping of G played a vital catalytic role in improving the dehydrogenation properties of MgH2 . SEM (scanning electron microscopy) observations revealed that G sheets were dispersedly embedded in MgH2 particles, which effectively inhibited the agglomerating of MgH2 particles during ball milling. XRD (X-ray diffraction) analyses showed that no new phases formed due to the immiscibility between MgH2 (Mg) and G. DSC (Differential Scanning Calorimetry) and DTG (Differential Thermal Gravity) measurements indicated the initial dehydrogenation temperatures of MgH2 -G composites were decreased and their dehydrogenation rate were also increased relative to pure-milled MgH2 . The mechanisms analyses based on first-principles calculations suggested that the improved dehydrogenation properties of MgH2 -G composites should be ascribed to the reduced dehydrogenation enthalpy and dehydrogenation activation energy of MgH2 upon the catalytic role of G. Highlights: Catalytic mechanisms of graphene on dehydrogenation properties of MgH2 were studied. Doped graphene inhibited the agglomerating of MgH2 particles during ball milling. No new phases formed due to the immiscibility between MgH2 (Mg) and graphene. Dehydrogenation temperature was decreased and dehydrogenation rate was increased. Dehydrogenation enthalpy and activation energy determine dehydrogenation properties.